PP.21.11: EFFICACY AND SAFETY OF FIXED-DOSE COMBINATION OF IRBESARTAN/ROSUVASTATIN IN PATIENTS WITH HYPERTENSION AND DYSLIPIDEMIA. (June 2015) - Kim, S.; Lee, H.L.; Kim, H.R.; Seo, J.B.; Chung, W.Y.; Zo, J.H.; Kim, M.A.
Abstract : Objective: This study was designed to evaluate the efficacy and safety of fixed dose combination of irbesartan and rosuvastatin and compare its characteristics with those of monotherapy with atorvastatin or irbesartan. Design and method: This is the prospective randomized double blind, multicenter trial of fixed dose combination. We enrolled the patients in 10 centers including Boramae hospital. Antihypertensive efficacy of fixed dose combination of rosuvastatin/irbesartan was compared with that of rosuvastatin. Primary evaluation points were 1) percent reduction of low-density lipoprotein cholesterol (LDL-C) in the rosuvastatin/irbesartan combination and irbesartan monotherpay after 8 weeks' treatment, and 2) percent reduction of sitting diastolic blood pressure (siDBP) in the rosuvastatin/irbesartan combination and rosuvastatin monotherapy after 8 weeks' treatment. Secondary evaluation points were other lipid profile, systolic blood pressure and safety profile. Results: A total of 733 patients with comorbid hypertension and hyperlipidemia were screened and 230 patients were eligible for this randomized, double-blind, Phase III study. 230 patients with hypertension and hypercholesterolemia were randomized into 6 groups 1) rosuvastatin 10 mg, 2) irbesartan 300 mg, 3) rosuvastatin 10 mg / irbesartan 150 mg, 4) rosuvastatin 10 mg/irbesartan 300 mg, 5) rosuvastatin 20 mg / irbesartan 150 mg, 6) rosuvastatin 20 mg/irbesartan 300 mg). After 8 weeks' treatment, LDL-C level decreased significantly in rosuvastatin 10 mg / irbesartan 300 mg and rosuvastatin 20 mg/irbesartan 300 mg compared with that of irbesartan 300 mg monotherapy (−47.8% and −51.8% vs −2.7%, p < 0.001). After 8 weeks' treatment, siDBP decreased significantly in rosuvastatin 10 mg / irbesartan 150 mg and rosuvastatin 10 mg/irbesartan 300 mg compared with that of rosuvastatin 10 mg monotherapy (−9.5% and −11.7% vs −3.4%, p < 0.05). Reduction of siDBP after 8 weeks was 8.50 mmHg in the IRB300 + ATO40 group and 10.66 mmHg in the IRB300 + ATO80 group in comparison with 8.40 mmHg in the IRB300 group.There was no significant difference in the adverse event rates between groups. Conclusions: Fixed dose combination of rosuvastatin/irbesartan was more effective in lowering blood pressure and LDL-C level than monotherapy groups. There was no significant difference in the safety between groups.